Review of Techniques Currently Used for Treatment of Domestic Waste Water - Shrivastava, Preeti; Vichare, S. (International Journal of Engineering and Technology, 2018)
Nowadays, the main problem faced by WWT (Waste Water Treatment) plants all over the world is the large amount of energy consumed and the ineffectiveness in treating Contaminants of Emerging Concern (CECs) the presence of which is constantly increasing in the municipal waste water. The conventional treatment method also requires large amounts of lands making the entire treatment process very costly. Alternate methods like use of ozone is showing promising results. The objective of this paper is to review the various techniques for the treatment of municipal waste water mainly for the removal of heavy metals and CECs and the energy consumed.Â